Half a century of IgA nephropathy: achievements, frustrations and challenges - I.I. Lapchynska (Ukrainian Journal of Nephrology and Dialysis, 2018)
IgA nephropathy is the most common glomerulonephritis worldwide. This disease has a tremendous economic impact because renal replacement therapy is expensive and hard-to-reach. It also represents a social problem because children and young adults in their second and third decades of life are affected by the IgA nephropathy, and it is the most active period of human life with highest work productivity. Many retrospective studies have shown that 40% of biopsy-proven IgA nephropathy patients develop end-stage kidney disease in 20 years after their biopsy disease. The biomarker research in IgA nephropathy has experienced a major splash in recent years with great number of scientific reports. Individual biomarkers often lack sensitivity and specificity with impairment of disease specificity as a consequence. The review describes a novel approach based on a panel of biomarkers for pathogenic process of IgA nephropathy. Integration of genetic, clinical, and bioinformatics data sets could optimize the specific value of each biomarker in a multimarker panel. This is a inspirational and promising approach for precision medicine and personalized therapy in IgA nephropathy. Half a century into the original description of IgA nephropathy, there is still no specific therapy for this condition Although the scarcity in treatment advances could be related to the disease’s complex pathogenesis. The evolution of different therapeutic approaches is reviewed over time and resulted in the 2012 Kidney Disease: Improving Global Outcomes Clinical Practice Guideline for Glomerulonephritis that presently is being updated, and provide collation of recent data on various forms of immunosuppressive agents. Existing approaches to treatment of IgA nephropathy are described with focus primarily on innovative therapeutic strategies currently being evaluated in IgA nephropathy that were not discussed in the 2012 Kidney Disease Improving Global Outcomes Clinical Practice Guidelines.